2019
DOI: 10.1016/j.urology.2019.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Sexual Outcomes Following Bulbar Urethroplasty–An Analysis of 2 Common Approaches

Abstract: OBJECTIVETo report success and patient reported urinary and sexual outcomes of patients who underwent anastomotic urethroplasty and dorsal buccal onlay urethroplasty. MATERIALS AND METHODSPatients who underwent primary transecting anastomotic or dorsal buccal onlay urethroplasty for bulbar strictures at our institution between 1998 and 2015 were analyzed. Patients who had a prior urethroplasty, involvement of a different portion of the urethra, or a diagnosis of lichen sclerosis (LS) or hypospadias were exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 15 publications
(15 reference statements)
2
26
0
2
Order By: Relevance
“…In another comparison of EPA vs. dorsal graft urethroplasty, Furr et al (38) reported decreased glans filling in 10.6% and 9.4% of patients, respectively. They also found decreased penile sensation in 23.4% and 18.8% of EPA and grafting cohorts.…”
Section: Cold Glans Sensation and Decreased Penile Sensitivitymentioning
confidence: 97%
See 3 more Smart Citations
“…In another comparison of EPA vs. dorsal graft urethroplasty, Furr et al (38) reported decreased glans filling in 10.6% and 9.4% of patients, respectively. They also found decreased penile sensation in 23.4% and 18.8% of EPA and grafting cohorts.…”
Section: Cold Glans Sensation and Decreased Penile Sensitivitymentioning
confidence: 97%
“…Furr et al (38) reported sexual results of their cohort of bulbar urethroplasties using EPA (96 patients) vs. dorsal BMG urethroplasty (32 patients). There were no significant differences between groups regarding IIEF5 postoperative score (BMG 18.4 vs. EPA 17.1), patients with IIEF5 >15 (BMG 69% vs. EPA 69%), potency or difficulty achieving erections (BMG 31% vs. EPA 27%).…”
Section: Erectile Function After Different Surgical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…performed a retrospective analysis of patients operated between 1998 and 2015 (40 underwent DBOU, Group I, while 139 AU, Group II) to compare the success and patient-reported urinary and sexual outcomes between the two methods. [18] The long-term success was 95% and 99.3% ( P = 0.06), with a mean follow-up of 51.4 and 63.3 months in Groups I and II, respectively. Patient-reported outcomes were similar in both the groups.…”
Section: Sexual Functions Following Anastomotic Urethroplastymentioning
confidence: 99%